Clairvoyance and Occult Powers - Atkinson, William Walker, 1862-1932 (Salt Lake City, UT : Project Gutenberg, 2004)
"Clairvoyance and Occult Powers" by William Walker Atkinson is a comprehensive guide on psychic phenomena written in the early 20th century. This work serves as a manual for individuals interested in developing their psychic abilities, focusing on various aspects of clairvoyance, telepathy, and related occult practices. The text delves into the different forms of extra-sensory perception, discussing methods for enhancing one's psychic faculties and understanding the underlying principles of these phenomena. The opening portion of the book introduces readers to Atkinson's premise that human beings possess more than just the five physical senses. He emphasizes the concept of "astral senses," which function on a higher plane of consciousness, allowing individuals to perceive reality beyond ordinary sensory limitations. The text sets the stage for a systematic exploration of various psychic abilities, including telepathy and clairvoyance, asserting that these skills can be cultivated through practice and understanding. Atkinson's writing highlights the need for an open mind toward these possibilities and encourages readers to engage with their intuitive faculties as a means of accessing deeper truths about existence. (This is an automatically generated summary.)
Release date is 2004-05-01
E-text prepared by Julie Barkley, Sjaani, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Clairvoyance